Revisiting the European Union framework on immigrant integration: The European integration forum as a technology of agency. (August 2014) - Arribas Lozano, Alberto; García-González, Nayra; Sebastiani, Luca; Álvarez Veinguer, Aurora; Gil Araujo, Sandra
In the last 15 years, a European Framework on Immigrant Integration has been developed through soft law tools, aiming to create a common understanding of the concept and promoting the coordination, funding, and exchange of best practices among states, local administrations, and nongovernmental actors. In this article, we first contextualize the emergence of immigrant integration policies at the European Union level. We then examine the principal European Union documents on this issue, paying special attention to the link between integration and immigrant participation. Finally, based on an empirical study, we analyze, from the perspective of governmentality, the European Integration Forum, an apparatus considered the "last word" in immigrant integration policies at the European Union level.